Hydrothermal waters enriched in silica promote the development of a sponge community in North Sulawesi (Indonesia). Issue 1 (1st January 2017) - Bertolino, M.; Oprandi, A.; Santini, C.; Castellano, M.; Pansini, M.; Boyer, M.; Bavestrello, G.
Abstract: Two shallow hydrothermal vents were investigated by SCUBA diving to evaluate their influence on the structure and diversity of a sponge community living close to the vent outflow, in the equatorial Pacific Ocean just off the coast of North Sulawesi, Indonesia (1Â°40.361Ê¹N, 125Â°8.112Ê¹E). No sponges identified were vent-obligate species, since they are found in the surrounding coral reefs too. The sponges were strongly attracted by the vent, concentrating in an area of a few meters around it, where they reached covering values up to 70% in the deeper vent and up to 42% in the shallower one. The high silica concentration, 8.5Â mg L âˆ'1 Si (deep vent) and 5Â mg L âˆ'1 Si (shallow vent), in hot spring water (90Â°C) was the putative environmental factor driving the sponge settlement and growth. These organisms take advantage of the increased silica availability that, facilitating skeleton formation, probably promotes sponge growth. This hypothesis is in agreement with the evidence that the spicules of the sponge specimens living around the hot springs have a thickness about double that of conspecific specimens present on the coral reefs at least 300Â m away.